2019
DOI: 10.3390/toxins11060337
|View full text |Cite
|
Sign up to set email alerts
|

Cold Plasma Treatment as an Alternative for Ochratoxin A Detoxification and Inhibition of Mycotoxigenic Fungi in Roasted Coffee

Abstract: Ochratoxin A (OTA) produced by mycotoxigenic fungi (Aspergillus and Penicillium spp.) is an extremely toxic and carcinogenic metabolite. The use of cold plasma to inhibit toxin-producing microorganisms in coffee could be an important alternative to avoid proliferation of mycotoxigenic fungi. Roasted coffee samples were artificially inoculated with A. westerdijikiae, A. steynii, A. versicolor, and A. niger, and incubated at 27 °C over 21 days for OTA production. Samples were cold plasma treated at 30 W input po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…As for the last-mentioned item, NTP has big potential to reduce the volume of mycotoxins by both fungi reduction and mycotoxins degradation with high potential for practical applications during the whole food production chain. The most recent studies [ 48 , 49 , 50 , 51 ] suggest practical applications of NTP to degrade mycotoxins on roasted coffee, hazelnuts, maize, and rice. The list of these studies can be found in Table 1 .…”
Section: Non-thermal Plasma Ntpmentioning
confidence: 99%
“…As for the last-mentioned item, NTP has big potential to reduce the volume of mycotoxins by both fungi reduction and mycotoxins degradation with high potential for practical applications during the whole food production chain. The most recent studies [ 48 , 49 , 50 , 51 ] suggest practical applications of NTP to degrade mycotoxins on roasted coffee, hazelnuts, maize, and rice. The list of these studies can be found in Table 1 .…”
Section: Non-thermal Plasma Ntpmentioning
confidence: 99%
“…Cold plasma technologies are being widely tested on seeds to enhance the germination rate and plant growth [23][24][25][26][27]. They have been also applied for inactivating pathogenic and spoilage microorganisms in food [28][29][30]. All proposed applications of cold plasma technology for agriculture, including water treatments, are presented in Puac et al [31].…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in sterilization technologies in the last decade focuses on the following factors: low temperature operation so that the technology is suitable for a variety of materials, shorter cycles of operation for faster sterilization, environmental friendliness, and cost reduction (Bunz et al 2018). Cold plasma can be a useful tool for destroying all types of pathogenic micro-organisms (Bunz et al 2018;Nasir et al 2016;Casas-Junco et al 2019). Cold plasma can be used in vacuum as well as in atmospheric pressure (Barve et al 2017;Kar et al 2018;Sharma et al 2017Sharma et al , 2018.…”
Section: Introductionmentioning
confidence: 99%